Literature Riview: Material Flow Cost Accounting (MFCA) - Suci Ramadhani; Rara Baitul Yuli Aprian; Zul Azmi (CV. ITTC INDONESIA, 2026)
The rapid growth of industrial activities has led to increased energy consumption and intensive exploitation of natural resources, resulting in environmental degradation such as waste pollution and declining ecosystem quality. This condition encourages companies to implement cost management systems that are not only profit-oriented but also emphasize efficiency and environmental sustainability. One relevant approach is Material Flow Cost Accounting (MFCA), an environmental management accounting method that tracks material and energy flows in production processes to identify inefficiencies, waste generation, and potential cost savings. This study aims to review existing literature on the implementation of MFCA in improving cost efficiency, waste management, and corporate sustainability, as well as to analyze its relationship with Green Accounting. The research employs a literature review method by critically analyzing and synthesizing relevant national and international journal articles. The findings indicate that MFCA effectively enhances material and energy efficiency, reduces waste generation, and positively contributes to corporate profitability and firm value. Furthermore, the integration of MFCA with Green Accounting strengthens corporate sustainability performance through improved environmental cost transparency and more responsible decision-making. Therefore, MFCA can be considered a strategic tool for supporting sustainable industrial development.